2020
DOI: 10.7554/elife.50434
|View full text |Cite
|
Sign up to set email alerts
|

ARL13B regulates Sonic hedgehog signaling from outside primary cilia

Abstract: ARL13B is a regulatory GTPase highly enriched in cilia. Complete loss of Arl13b disrupts cilia architecture, protein trafficking and Sonic hedgehog signaling. To determine whether ARL13B is required within cilia, we knocked in a cilia-excluded variant of ARL13B (V358A) and showed it retains all known biochemical function. We found that ARL13BV358A protein was expressed but could not be detected in cilia, even when retrograde ciliary transport was blocked. We showed Arl13bV358A/V358A mice are viable and fertile… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(88 citation statements)
references
References 82 publications
4
69
1
Order By: Relevance
“…These results are compatible with the fact that the phenotypes of INPP5E -KO and ARL13B -KO cells closely resemble each other ( Figs 2 and 3 ). In this context, it is important to note the recent study of Gigante et al showing that knockin mice of Arl13b(V358A), which is an Arl13b variant defective in ciliary localization due to a Val-to-Ala substitution in the VxP ciliary targeting motif ( Higginbotham et al, 2012 ), showed apparently normal Hh signaling, even though ciliary localization of INPP5E was not observed ( Gigante et al, 2020 ). Thus, similarly to INPP5E(ΔCTS), the cilia-excluded Arl13b(V358A) variant might be able to enter cilia but unable to be retained on the ciliary membrane, although it is unknown as to how the VxP motif participates in the ciliary targeting of ARL13B.…”
Section: Discussionmentioning
confidence: 99%
“…These results are compatible with the fact that the phenotypes of INPP5E -KO and ARL13B -KO cells closely resemble each other ( Figs 2 and 3 ). In this context, it is important to note the recent study of Gigante et al showing that knockin mice of Arl13b(V358A), which is an Arl13b variant defective in ciliary localization due to a Val-to-Ala substitution in the VxP ciliary targeting motif ( Higginbotham et al, 2012 ), showed apparently normal Hh signaling, even though ciliary localization of INPP5E was not observed ( Gigante et al, 2020 ). Thus, similarly to INPP5E(ΔCTS), the cilia-excluded Arl13b(V358A) variant might be able to enter cilia but unable to be retained on the ciliary membrane, although it is unknown as to how the VxP motif participates in the ciliary targeting of ARL13B.…”
Section: Discussionmentioning
confidence: 99%
“…Given the ciliary function of Arl13 (see above), we speculate that the DD_RI_PKA domain in some Arl13 proteins interacts with a cilium-localized AKAP, such as the aforementioned RSP3 protein (Gaillard et al, 2001;Jivan et al, 2009). In contrast, mammalian Arl13b contains the simpler VxP motif in the large C-terminal domain that is required for ciliary localization (Higginbotham et al, 2012;Cevik et al, 2013;Gigante et al, 2020). DD_RI_PKA domains in Phytophthora sojae Arl13 are followed by the TUDOR domain, known for the ability to bind to the methylated lysine and/or arginine residues (Botuyan and Mer, 2016).…”
Section: Extensive Diversity Of Multi-domain Arf Family Membersmentioning
confidence: 99%
“…To directly ask whether ARL13B mediates SCP guidance to the dorsal thalamus from within cilia, we examined a mouse expressing a cilia-excluded variant of ARL13B, ARL13B V358A (Figure 2) (Gigante et al 2020). We previously demonstrated that ARL13B V358A retains all known ARL13B biochemical activity, is undetectable in cilia yet transduces vertebrate Hh signaling normally (Mariani et al 2016; Gigante et al 2020). We found that either dorsal or ventral thalamus injections resulted in visible clusters of dye-stained cells in the contralateral DCN in control (Figure 2A-B, dorsal: 3/3; ventral: 5/5) and Arl13b V358A/V358A (Figure 2C-D, dorsal: 3/3; ventral: 3/3) animals.…”
Section: Resultsmentioning
confidence: 99%
“…Note that Arl13b Δ is the deletion allele resulting from germline deletion of the conditional Arl13b flox allele. Genotyping was as previously described (Heydemann et al 2001; Goebbels et al 2006; Nolan-Stevaux et al 2009; Su et al 2012; Gigante et al 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation